1991
DOI: 10.1007/bf00231768
|View full text |Cite
|
Sign up to set email alerts
|

Topographic relationship between sagittal Purkinje cell bands revealed by a monoclonal antibody to zebrin I and spinocerebellar projections arising from the central cervical nucleus in the rat

Abstract: We have examined the topographic relationship between the sagittal bands of zebrin I immunoreactive Purkinje cells revealed by a monoclonal antibody, mabQ113, and the distribution of spinocerebellar fibers originating from the central cervical nucleus in the rat. The mossy fiber terminals were anterogradely labeled following injections of cholera toxin subunit B into the C1-C3 segments and visualized immunohistochemically. Zebrin I positive Purkinje cells appeared in seven sagittal bands (P1+ to P7+ bands). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…In group I, the v-PO, d-PO, r-MAO, and subnucleus a receive input from the cerebral cortex relayed by nuclei in the mesodiencephalic junction (Swenson and Castro, 1983;Onodera, 1984;Holstege and Tan, 1988;de Zeeuw, 1989) (Fig. 8 B, green arrows), although the subnucleus a also receive input from the spinal cord (Matsushita et al, 1991).…”
Section: Organization Of the Inferior Olive: Five Groups Related To Dmentioning
confidence: 99%
See 1 more Smart Citation
“…In group I, the v-PO, d-PO, r-MAO, and subnucleus a receive input from the cerebral cortex relayed by nuclei in the mesodiencephalic junction (Swenson and Castro, 1983;Onodera, 1984;Holstege and Tan, 1988;de Zeeuw, 1989) (Fig. 8 B, green arrows), although the subnucleus a also receive input from the spinal cord (Matsushita et al, 1991).…”
Section: Organization Of the Inferior Olive: Five Groups Related To Dmentioning
confidence: 99%
“…Among these molecules is zebrin II (Brochu et al, 1990;Hawkes, 1997), which has been shown to be aldolase C (Ahn et al, 1994). Although several studies have shown parallels between zebrin compartments and the climbing and mossy fiber projection patterns in some areas of the cerebellar cortex (Gravel et al, 1987;Matsushita et al, 1991;Voogd and Ruigrok, 1997;Voogd et al, 2003), a systematic comparison throughout the cerebellar cortex has not yet been made. Thus, the significance of zebrin compartments in terms of cerebellar morphology and physiology is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…The granular layer is also subdivided into stripes (for review, see Ozol and Hawkes, 1997) that also align with the overlying Purkinje cell compartments [e.g., mossy fiber terminal fields (Matsushita et al, 1991;Akintunde and Eisenman, 1994;Ji and Hawkes, 1994;Voogd et al, 2003;Pijpers et al, 2006)], and an elaborate mosaic of patches is revealed both in tactile receptive field maps (Welker, 1987) and by histological treatments (Hawkes et al, , 1998. Finally, functional studies have also demonstrated parasagittal stripes in the cerebellum Larson, 1973, 1980) (for review, see Voogd et al, 1996) with direct correlations with particular Purkinje cell stripes (Chockkan and Hawkes, 1994;Chen et al, 1996;Hallem et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The complex interactions occurring during these early time points generate the specific connectivity patterns evident in the adult central nervous system (Belford and Killackey, 1979;Hubel and Wiesel, 1977;Sperry, 1963, Woolsey andVan der Loos, 1970). Investigations of the cere-0 1993 WILEY-LISS, INC bellum have identified several afferents which are topographically organized (Epema et al, 1985;Gerrits et al, 1985;Kerr and Bishop, 1991;Matsushita et al, 1991;Russchen et al, 1976;Voogd et al, 1969), including the olivocerebellar projection (see Brodal and Kawamura, 1980, for a review). Unlike the other major cerebellar afferent, the mossy fibers, olivocerebellar fibers are derived from a single source, the inferior olivary complex (Desclin, 1974).…”
Section: Introductionmentioning
confidence: 99%